The Implementation of Quizizz Game toward Students’ and Teacher’s Motivation in English Classes at Kampung Inggris Semarang - nurlela, wilis; Rudi Hartono; Frimadhona Syafri (English Education Journal, 2024)
This research aims to investigate the implementation of Quizizz in English classes, the students’ motivation and teacher’s motivation toward Quizizz in online and offline learning. The research applies a qualitative study in Kampung Inggris Semarang. The data were taken from interview, observations, and questionnaire. This study shows that the implementation of Quizizz game toward students’ and teacher’s motivation in English classes can assist in the learning process, increase their engagement, increse their comfortability in the learning process, encourage them in the learning process, and afftect their concentration. The result shows that when Quizizz were applied appropriately, they could enhance students’ and teacher’s motivation. In addition, the implementation of Quizizz in proper way could also increase both students’ and teacher’s motivation in English classes. This study suggests that the appropriate application of Quizizz Game can be  an alternative way that enhance students’ motivation.